Pengembangan Metode KEPOKPEDAS dalam Meningkatkan Kecerdasan Personal pada Pembelajaran PAI Siswa Kelas V SDN Krapyak - Poniran Poniran; Mhd. Lailan Arqam; Miftachul Huda; Djamaluddin P (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
This study aims to develop a cooperative learning method using the Student Teams Achievement Division (STAD) method into the Intelligent Personal Group Cooperation (KEPOKPEDAS) method in PAI, as well as to measure the effectiveness of the KEPOKPEDAS method in improving the personal intelligence of Class V Elementary School students. The type of research used is R & D which consists of 10 development steps. The subjects of the study were fifth grade students at the Krapyak Godean State Elementary School. The object of this research is the learning process of the KEPOKPEDAS method to improve personal intelligence. Data collection techniques in the form of observation, interviews, questionnaires and documentation. Analysis of data collection was carried out using the interaction model developed by Milles and Hubermen. The results showed that the KEPOKPEDAS method had sufficient feasibility based on the validation scores of Material Expert 3.5, Method Expert 4.1, limited field test 4.03, and main trial 4.1, with an average of 3.93 (enough). While the effectiveness of the method in improving personal intelligence has a significant effect based on the comparison of the initial test results 80.07 with the final test of 85.13 which is included in the effectiveness of the 2016 PSS Paired Samples Test results: the acceptance of the Ttable calculation is greater than Tcount, which is 0.000Ë‚0.05. Thus the application of the KEPOKPEDAS method to increase personal intelligence is effective.